Statement by the Managing Director on the Independent Evaluation Office Report on IMF Exchange Rate Policy Advice : Revisiting the 2007 IEO Evaluation. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2017)
I would like to thank the Independent Evaluation Office (IEO) for preparing this informative and timely report, which provides an update on the IMF's progress in its approach to exchange rate policy advice since 2007. I am pleased with its main finding that the IMF has substantially overhauled its approach to exchange rate policy advice, and concur that some issues need our continued attention. I would like to note that management and staff remain fully committed to the role of the External Sector Report (ESR) in Fund surveillance.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: Advice; Fund Surveillance; IEO Evaluation; Policy Advice; PP